Pengaruh Model Cooperative Learning Tipe Artikulasi Terhadap Hasil Belajar Siswa di Sekolah Dasar - Agasi, Diren; Desyandri, Desyandri; Fachrudin, Farida (Universitas Negeri Padang, 2018)
The study aims to determine the effect of model cooperative learning outcomes of students for citizenship education on concept simple example of globalization effect in the circles. The method used is a quasipexperimental methods. This study was conducted in SDN 02 and 05 Sialang. In this research have two sample is the experimental and control group with 31 students. The experimental group used the cooperative learning tipe of articulation model and the control group used approach conventional group. Base on data analysis using t-test, indicates that the learning outcomes of students who are taught model cooperative learning obtained tcount 6,3655 dan ttable 2. With the result that tcount>ttable, it can be concluded that there is significant relationship between learning cooperative learning type of articulation model on students learning outcomes.